Strengthening research capacity: a systematic review of manuscript writing and publishing interventions for researchers in low-income and middle-income countries. Issue 2 (14th February 2022) - Busse, Clara E; Anderson, Elizabeth W; Endale, Tamrat; Smith, Yolanda Regina; Kaniecki, Marie; Shannon, Carol; August, Ella T
Abstract : Introduction: Health researchers from low-income and middle-income countries (LMICs) are under-represented in the academic literature. Scientific writing and publishing interventions may help researchers publish their findings; however, we lack evidence about the prevalence and effectiveness of such interventions. This review describes interventions for researchers in LMICs aimed at strengthening capacity for writing and publishing academic journal articles. Methods: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to report literature searches in PubMed, Embase, Global Health, Scopus and ERIC. Our keywords included LMICs, low-income and middle-income countries, health research and writing/publication support interventions, with no restrictions on publication date. Our screening process consisted of title screening, abstract review and full-text review. We collected information about the content, implementation and evaluation of each intervention, if included. Results: We identified 20 interventions designed to strengthen capacity for scientific writing and publishing. We summarised information from the 14 interventions that reported submitted or published papers as outcomes separately, reasoning that because they provide quantifiable metrics of success, they may offer particular insights into intervention components leading to publication. The writing and publishing components in this 'Publications Reported' group were an average length of 5.4 days compared with 2.5 days in the other group we refer to as 'Other Interventions.' Whereas all 14 Publications Reported interventions incorporated mentors, only two of five in the Other Interventions group incorporated mentors. Across interventions, leaders expressed the importance of a high ratio of mentors to participants, the need to accommodate time demands of busy researchers, and the necessity of a budget for open access fees and high-quality internet connectivity. Conclusion: Writing and publishing interventions in LMICs are an underutilised opportunity for capacity strengthening. To facilitate the implementation of high-quality interventions, future writing and publishing interventions should share their experiences by publishing detailed information about the approach and effectiveness of the interventions.